Penerapan Model Project Based Learning (PjBL) dalam Peningkatan Keaktifan dan Hasil Belajar Siswa pada Pembelajaran Pendidikan Pancasila di Kelas VB UPT SDN 064034 Medan Johor - Tarigan, Anjelia; Panjaitan, Dedy Juliandri; Nurmairina, Nurmairina; Saragih, Agung Evansiyus (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study is motivated by the low student activity and learning outcomes in Civic Education, particularly on the topic of Indonesian cultural diversity in grade 5 at UPT SDN Negeri 064034 Medan Johor. The purpose of this research is to examine the effectiveness of implementing the Project Based Learning (PjBL) model in improving student engagement and learning outcomes. The research method used is Classroom Action Research (CAR) involving 25 students. Data on student activity were collected through observations based on indicators such as asking questions, answering, discussion, assignments, and group participation, analyzed across three phases: pre-action, cycle I, and cycle II. The data is analyzed using quantitative descriptive methods. The results indicate an increase in average student activity scores from 6.0 in the pre-action phase to 6.7 in cycle I, and reaching 7.8 in cycle II, with the number of students categorized as highly active increasing from 6 to 13. The implementation of PjBL proved effective in enhancing active student involvement, making the learning process more interactive and collaborative. This conclusion supports that the PjBL model is an appropriate learning strategy to improve the quality of Civic Education in elementary schools.